Peran Voucher Diskon, Gratis Ongkir, dan Penilaian Produk terhadap Pembelian Impulsif GoFood di Kota Tangerang - Aulia Fikri, Hikmal; Hamdani, Hamdani; Rauf, Abdul (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
This study aims to analyze the effect of discount vouchers, free shipping, and product ratings on impulse purchases of GoFood consumers, both partially and simultaneously. The method used is a quantitative approach with multiple regression analysis techniques through the SPSS version 30 application. The research sample consisted of 130 respondents selected using nonprobability sampling techniques. Data were collected through a closed questionnaire distributed online. The results of the analysis show that the three independent variables, namely discount vouchers, free shipping, and product ratings, have a positive and significant influence on impulse purchases partially. Simultaneously, the three variables also show a significant influence on impulse buying behavior. These findings suggest that consumers tend to make unplanned purchases when they receive attractive offers and see positive product reviews. The implication of this study is the importance of promotion-based marketing strategies and product reputation in encouraging impulse buying.